Racism and discrimination in the care of Totonaca women in Veracruz, Mexico: the need for intercultural competencies - Niels Michael Dörr; Gunther Dietz (Social Medicine Publication Group, 2022)
Target. Racism is a health inequality that has been neglected. The objective is to examine maternal health in rural Mexico with respect to the different forms of discrimination. Material and methods. The research is based on anthropological fieldwork carried out in the Sierra del Totonacapan region in Veracruz, Mexico. Results. We empirically distinguish and document omissions and violations of human rights, before analyzing the sources of racism from an intersectional perspective, according to which gender, class and race constitute closely linked sources of discrimination. Conclusions. Finally, we propose an intercultural competence approach to confront racism at its confluence with other ideologies. This approach is aimed at professionals as conscious, reflective and transforming actors of intercultural interactions.